College as Country Club: Do Colleges Cater to Students’ Preferences for Consumption? - Jacob, Brian; McCall, Brian; Stange, Kevin (Journal of Labor Economics, 2018)
This paper investigates whether demand-side market pressure explains colleges’ decisions to provide consumption amenities to their students. Using a discrete choice model of college demand, we find that most students appear to value consumption amenities, such as operating spending on student activities, sports, and dormitories, while the taste for academic quality is confined to high-achieving students. Heterogeneity in student preferences creates variation in demand pressure across institutions, which we estimate can account for 11% of the total variation in the ratio of amenity to academic spending across 4-year colleges in the United States.